Association Between Dopaminergic Medications and the Evolution of REM Sleep Behavior Disorder in Parkinson's Disease - Cao, Ruihua; Ma, Ruolin; Wang, Kai; Hu, Panpan (Frontiers in Neurology, 2022)
REM sleep behavior disorder (RBD) is closely associated with Parkinson's disease (PD), however, the influence of dopaminergic replacement therapy (DRT) on the clinical course of RBD in PD remains less understood. The objective of our study is to investigate how DRTs modify the evolution of RBD in a longitudinal cohort study of initially de novo PD patients. Four hundred and five drug-naive patients with early-stage PD were included. RBD symptoms were assessed using the 10-item RBD Screening Questionnaire (RBDSQ) at baseline and during the 5-year follow-up. A generalized estimating equation was used to examine predictors of the evolution of RBD symptoms. For patients without baseline pRBD, patients on levodopa treatment showed a greater increase in RBDSQ scores than those not on levodopa treatment, and the increase in RBDSQ scores was significantly correlated with the levodopa-LEDD. Moreover, the changes in RBDSQ scores at a given post-baseline visit were significantly associated with the use of levodopa (OR = 1.875, p = 0.008) and the combined use of levodopa and DA (OR = 2.188, p = 0.012), as well as the levodopa-LEDD (OR = 1.001, p = 0.005) at that visit. The use of DA alone or the DA-LEDD was not a significant predictor of changes in RBDSQ scores. Similarly, a conversion from pRBD negative to pRBD positive was significantly associated with levodopa-LEDD (OR = 1.001, p = 0.014) but not DA-LEDD. Together, these finding implicated that the use of levodopa may act as a contributing factor to the increasing prevalence of RBD after the onset of PD, suggesting different mechanisms underlying prodromal RBD and late-onset RBD.